Makna Simbol Budaya Lokal Bagi Komunitas Tanah Aksara - Dhita Prasanti; Nuryah Asri Sjafirah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2017)
In this modern era, as culture evolves into a popular culture mixed with western culture, there is still a community that wants to maintain the tradition of local cultural heritage, in the field of literacy. This is also reflected in a study that will raise researchers this time. The community is called â€œTanah Aksaraâ€. Researchers raised research on the Meaning of Local Culture Symbol for â€œTanah Aksaraâ€ Community in Bandung. â€œTanah Aksaraâ€ has its own characteristic in Bandung, which upholds the cultural heritage of the local script. They have peculiarities that characterize their identity through the attributes of clothing or other symbols that characterize the main individual in the â€œTanah Aksaraâ€ community. In this study, researchers used a qualitative approach with qualitative descriptive method. Data collection techniques used were interviews, observation and documentation. Data analysis techniques used are observation persistence, data triangulation, and referential adequacy. Researchers use communication theory to analyze this research is the theory of symbolic interaction. The results of research that has been done by the researcher shows that the meaning of local culture for the Tanah Aksara community include: (1) Symbol as the formation of identity for the Tanah Aksara community; (2) Symbols as preservation of local traditions and cultures for Tanah Aksara communities; (3) Symbols as preservation of the script of the archipelago; (4) Symbols as symbols of ancestral heritage/ ancestors; (5) Symbols as an encouragement of social activities.